Interrelation of protein metabolism and autonomic nervous system in laying hens - Kulbako, O.; Karpovsky, V.; Zhurenko, O.; Hryshchuk, I.; Karpovsky, P.; Krivoruchko, D.; Hryshchuk, A. (Scientific Progress & Innovations, 2024)
The study of factors influencing the processes of protein metabolism in the poultry body will help to better balance the diet, which will help to more effectively stimulate the growth of animal productivity. The aim of the work was to investigate the role of the autonomic nervous system in protein metabolism and to take into account the individual characteristics of the poultry organism, characterized by different tone of the autonomic nervous system. The formation of experimental groups of animals was carried out by electrocardiographic examination using the Baevsky method, on the basis of which three experimental groups of animals were formed: normotonics, vagotonics, and sympathotonics. The blood serum was studied using a LabLine-010 spectrophotometer (Austria) and test systems from Laboratory Granum LLC, Kharkiv. Kharkiv. According to the results of the biochemical study, it was found that the content of total protein, which was compared with the experimental group of normotonics (46.10±1.35 g/l) with a balanced sympathovagal balance, was 14.8 % lower than that of the experimental group of sympathotonics (54.10±2.60 g/l) (P<0.01) and 18.1 % lower than that of the experimental group of vagotonics (56.30±1.90 g/l) (P<0.01). The albumin content, which was compared with the experimental group of normotonics (4.56±0.55 g/l) with a balanced sympathovagal balance, was 40.55 % lower than that of the experimental group of sympathotonics (6.96±0.49 g/l) (P<0.001) and 1.5 times lower than that of the experimental group of vagotonics (7.67±0.38 g/l) (P<0.01). The creatinine content compared to the normotonic group (47.12±0.77) with a balanced sympathovagal balance was lower than that of the experimental group by 6.77 % compared to the experimental group of vagotonic poultry (7.67±0.38 g/l) (P<0.001). Taking into account the individual characteristics of the poultry organism and establishing the tone of the autonomic nervous system, it was determined that the autonomic nervous system has an effect on protein metabolism in poultry. The prospect of further research is to study the use of nanoaquahelate preparations to improve productivity and metabolic processes, taking into account the tone of the autonomic nervous system.